2020
DOI: 10.1021/acs.nanolett.9b04798
|View full text |Cite
|
Sign up to set email alerts
|

Borophene Concentric Superlattices via Self-Assembly of Twin Boundaries

Abstract: Due to its in-plane structural anisotropy and highly polymorphic nature, borophene has been shown to form a diverse set of linear superlattice structures that are not observed in other two-dimensional materials. Here, we show both theoretically and experimentally that concentric superlattice structures can also be realized in borophene via the energetically preferred self-assembly of coherent twin boundaries. Since borophene twin boundaries do not require the creation of additional lattice defects, they are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…This increase is not surprising since it is consistent with the Bader charge analysis, where borophene donates a great amount of charge to NO 2 so that the valence electron has to overcome a greater total potential barrier to escape to the vacuum level. Given the fact that the calculated work function of pristine borophene is quite high ($5.0 eV), which is consistent with the experiment value of $4.9 eV, 65 the signicant enhancement of work function induced by the NO 2 adsorption is interesting.…”
Section: Impacts Of Vdw Functionals On Adsorption Propertiessupporting
confidence: 79%
“…This increase is not surprising since it is consistent with the Bader charge analysis, where borophene donates a great amount of charge to NO 2 so that the valence electron has to overcome a greater total potential barrier to escape to the vacuum level. Given the fact that the calculated work function of pristine borophene is quite high ($5.0 eV), which is consistent with the experiment value of $4.9 eV, 65 the signicant enhancement of work function induced by the NO 2 adsorption is interesting.…”
Section: Impacts Of Vdw Functionals On Adsorption Propertiessupporting
confidence: 79%
“…Since the end of the last century, boron nanostructures had been studied, which include zero‐dimensional (0D) clusters and one dimensional (1D) nanotubes. 2D boron sheets, as the most basic units for constructing the boron nanostructures, had attracted great attention in the past two decades . Especially, Boustani, Ismail‐Beigi and Yakobson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Excitingly, the hollow hexagons existing in triangular lattice also renders significant structure diversity of borophene. With the deepening of theoretical research, a plenty of unique physical and chemical properties in borophene have been reported, including highly anisotropic electronic structure, ultrahigh thermal conductance, mechanical compliance, phonon‐mediated superconductivity and optical transparency . These properties make borophene become an attractive material with potential applications in memory, superconducting devices and flexible electronics for quantum information technology .…”
Section: Introductionmentioning
confidence: 99%
“…The Mo movement in the p-GBs locally increases the energies of the two GBs by only 0.23 and 0.31 eV, respectively. According to transition-state theory 39,40 , we estimate the activating temperatures for the polygon migrations by X × exp(−Ebarrier/kBT) ≈ 1 with X ranging from ~10 12 to 10 15 . Estimated temperatures of 658-828 K and 480-600 K for forming the 4|4|4 and 8|8 motifs, respectively, are well below the experimental temperatures of ~973 K. The involved monatomic movement with relatively low energy barriers suggests a potential way to program the sequence of polygons: a STM tip scanning along the GBs.…”
Section: Fig2 | Structures and Energetics Of P-gbs In 2d Mose 2 Amentioning
confidence: 99%